2014
DOI: 10.1007/s00268-014-2536-9
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic Thyroid Carcinomas Incidentally Found on Postoperative Pathological Examination

Abstract: Incidental ATC is the only curable type of ATC, and further studies are needed to establish the effectiveness of additional postoperative radiotherapy and/or chemotherapy in incidental ATC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
0
14
2
Order By: Relevance
“…The other types, namely follicular and non-differentiated carcinoma, were found in 4% and 2% of the MNG patients, respectively. Yoshida et al [42] presented 675 cases of anaplastic TC, 5% of which were incidental in nature. They noted that for this type of thyroid malignancy, only incidental anaplastic carcinoma was curable.…”
Section: Discussionmentioning
confidence: 99%
“…The other types, namely follicular and non-differentiated carcinoma, were found in 4% and 2% of the MNG patients, respectively. Yoshida et al [42] presented 675 cases of anaplastic TC, 5% of which were incidental in nature. They noted that for this type of thyroid malignancy, only incidental anaplastic carcinoma was curable.…”
Section: Discussionmentioning
confidence: 99%
“…Up to half of ATC samples may contain a well‐differentiated component, usually antecedent or coexisting PTC and FTC, or occasionally a minor ATC component is found on postoperative pathological examination of patients with differentiated thyroid carcinoma . Recent Korean studies addressed a significance of coincident ATC and PTC/FTC .…”
Section: Anaplastic (Undifferentiated) Carcinomamentioning
confidence: 99%
“…193 Up to half of ATC samples may contain a well-differentiated component, usually antecedent or coexisting PTC and FTC, or occasionally a minor ATC component is found on postoperative pathological examination of patients with differentiated thyroid carcinoma. 194 Recent Korean studies addressed a significance of coincident ATC and PTC/FTC. 195,196 It was reported that pure ATC (100% undifferentiated component) and ATC arising from PTC/FTC (>10% undifferentiated component, usually > 50%) have a similar behavior and unfavorable prognosis.…”
Section: Anaplastic (Undifferentiated) Carcinomamentioning
confidence: 99%
“…It is then argued if incidental carcinomas also include the carcinomas discovered at the definitive histological examination, after total thyroidectomy for multinodular goiter (26)(27)(28)(29)(30)(31)(32)(33) or during treatment of an unrelated head and neck cancer (34). There is no doubt that the latter are also an occasional finding within parenchymas where multinodularity and poor response to medical therapy become responsible for an inalienable surgical choice.…”
Section: Introductionmentioning
confidence: 99%